'Ill Used by our Government': The Darien Venture, King William and the Development of Opposition Politics in Scotland, 1695–1701. (April 2019) - Comunale, Rachael E.
Abstract : This article examines the development of political opposition in Scotland from 1695 to 1701 in the context of the Company of Scotland Trading to Africa and the Indies. It is argued that the potency of the political movement inspired by Darien derived from the view that King William was directly implicated in the failure of the colony. Three episodes in the Company's history—the loss of subscriptions in Hamburg, the appearance of memorials in the new world prohibiting English aid to the colony and the imprisonment of Darien sailors by the Spanish authorities—are examined in detail. The ramification of these controversies was increasingly seen as the result not of English interference, but rather the crown's refusal to act on behalf of the Company. Because a significant proportion of the population was invested in the Company, and because the press helped to keep Darien in the forefront of public consciousness, these issues transformed Darien into a major political grievance that united disparate political factions in support of a single cause. Although the alliance inspired by Darien was temporary, it, nonetheless, played a crucial role in disrupting the political status quo.